Lime kiln denitration integrated flue gas treatment process
The lime kiln flue gas treatment process using honeycomb-plate composite modules and modified Ce-Mn/ZSM-5 catalysts solves the problems of catalyst poisoning and deactivation, poor low-temperature activity, and high ammonia escape rate in lime kiln flue gas, achieving a high-efficiency, low-energy denitrification effect, reducing equipment footprint, and extending catalyst life.
Patent Information
- Application Number
- CN202511106268.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-08
- Publication Date
- 2025-09-05
- Estimated Expiration
- 2045-08-08
AI Technical Summary
The high concentration of calcium-based dust in lime kiln flue gas causes poisoning and inactivation of traditional denitrification catalysts, poor low-temperature activity, high ammonia escape rate, high system energy consumption, and large equipment footprint. The existing modification technology is complex and costly, making it difficult to achieve industrial application.
A honeycomb-plate composite module catalyst is used in combination with a porous ammonia injection grid and an online NOx monitor. By modifying the Ce-Mn/ZSM-5 catalyst and utilizing the Ce4+/Ce3+ and Mn4+/Mn3+ redox cycles, the NH3/NOx molar ratio is controlled and integrated flue gas treatment is carried out in combination with a shell and tube waste heat boiler.
It achieves efficient and low-temperature denitrification, significantly reduces ammonia escape, reduces system energy consumption, shrinks equipment footprint, extends catalyst life, optimizes energy efficiency, and solves the technical difficulties in lime kiln flue gas treatment.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of industrial flue gas purification, and in particular to a lime kiln denitrification integrated flue gas treatment process. Background Art
[0002] In the field of industrial flue gas treatment, the denitrification treatment of lime kiln flue gas has always faced special challenges. Lime kiln flue gas contains high concentrations of calcium-based dust, which can easily cause poisoning and deactivation of traditional denitrification catalysts. Although conventional SCR denitrification processes are widely used in fixed sources such as power plants, when directly transplanted to lime kiln operating conditions, the catalyst life is often less than half a year. What's more tricky is that the temperature window of lime kiln flue gas is usually in the low temperature range of 180-250°C, which happens to be the temperature range where the activity of traditional vanadium tungsten titanium catalysts drops significantly. Existing technologies make it difficult to take into account the two key performance indicators of low-temperature activity and resistance to calcium poisoning.
[0003] Currently, lime kiln flue gas treatment mostly relies on a step-by-step dust removal and denitrification process, a solution with significant systemic flaws. While the dust removal-before-denitrification process can mitigate the direct impact of dust on catalysts, it increases the equipment footprint and significantly increases operating energy consumption. More seriously, the step-by-step treatment process presents significant ammonia slip, which not only wastes reducing agents but also creates secondary pollution. Some improvement proposals have attempted to add pretreatment equipment to the dust removal process, but the resulting increased pressure drop compromises the overall energy efficiency of the system. These technical bottlenecks have severely hampered the lime kiln industry's progress in achieving ultra-low emissions.
[0004] In recent years, researchers have conducted many explorations in catalyst modification, but none of them have been able to completely solve the special problems of lime kiln flue gas. Some studies have used molecular sieve carriers to load transition metal oxides. Although this has improved the low-temperature activity to a certain extent, its resistance to calcium ions is still insufficient. Other solutions protect the catalyst through surface coatings, but often at the expense of active site density. Existing modification technologies generally have problems of complex processes and high costs, making it difficult to achieve industrial application. Therefore, the development of a new treatment process that can adapt to the operating characteristics of lime kilns and has both high-efficiency denitrification performance and long-term stability has become a technical problem that urgently needs to be broken through in this field. Summary of the Invention
[0005] The purpose of the present invention is to provide a lime kiln denitrification integrated flue gas treatment process, which solves the problems of low low-temperature denitrification efficiency of existing lime kiln flue gas, catalyst calcium poisoning and deactivation, high ammonia escape rate, high system energy consumption, and large equipment footprint.
[0006] The present invention achieves the above-mentioned purpose through the following technical solutions: A lime kiln denitrification integrated flue gas treatment process comprises the following steps: S1, the flue gas enters the cyclone separator at a tangential velocity with a residence time of 2.5s; S2, processing the modified catalyst into a honeycomb-plate composite module; arranging it in layers according to the direction of flue gas flow, with the front 20% volume being a honeycomb structure and the rear 80% volume being a plate structure; S3, install a porous ammonia injection grid at the inlet of the cyclone reactor, according to the online NO x The monitor's real-time data dynamically adjusts the ammonia injection volume to maintain the NH3 / NO x The molar ratio is 0.9; S4, after denitrification, the flue gas enters the shell and tube waste heat boiler.
[0007] According to a preferred embodiment of the present invention, the cyclone separator is purchased from Zhangqiu Qun Yi Machinery Manufacturing Co., Ltd.
[0008] According to a preferred embodiment of the present invention, in step S1, the tangential velocity is 15 m / s; the diameter of the cyclone separator is 1.2 meters, and the height-to-diameter ratio is 3:1.
[0009] In this invention, when flue gas enters the cyclone separator at a specific tangential velocity, centrifugal force achieves gas-solid separation. The high tangential velocity creates a strong rotating flow field, causing dense lime dust particles to settle along the walls, while the purified flue gas forms an upward vortex and is discharged from the top. The optimized height-to-diameter ratio design prolongs particle residence time, ensuring adequate separation.
[0010] According to a preferred embodiment of the present invention, in step S2, the honeycomb-plate composite module has a pore density of 300 cpsi and a wall thickness of 0.3 mm.
[0011] The honeycomb-plate composite module in this invention features a front-stage honeycomb structure that generates turbulence through regular pores, enhancing the contact efficiency between flue gas and catalyst. The rear-stage plate structure reduces airflow resistance. This combined design ensures both reaction kinetics and optimized fluid dynamics. The specific pore density and wall thickness ensure sufficient specific surface area and mechanical strength.
[0012] The honeycomb structure described in the present invention is a monolithic catalyst support structure with a regular array of parallel pores. Its external form is a standard cylindrical or rectangular module, with a highly ordered hexagonal or square honeycomb grid arrangement in cross section. Each pore is a straight, parallel channel running straight through the airflow direction, separated by thin, uniform partitions. The pore density is precisely controlled to 300 pores per square inch (300 cpsi), with individual pores exhibiting a regular pore diameter of 1.2-1.5 mm and a uniform wall thickness of 0.3 mm. This structure utilizes a cordierite ceramic substrate coated with a 20-30 micron thick gamma-alumina transition layer as the active component carrier. The pore walls exhibit a hierarchical porous structure, comprising macropores of 10-20 microns, mesopores of 5-10 nanometers, and micropores less than 2 nanometers. This multi-scale pore system ensures an open porosity exceeding 70% while providing ample specific surface area. The channel connection nodes adopt an arc transition design and are locally thickened to 0.35 mm. At the same time, 0.1 mm high micro-guide fins are built in. While ensuring that the gas flow area accounts for more than 75%, a controllable turbulence effect is generated through the surface roughness of 5 microns. This carefully designed geometric structure keeps the hydraulic diameter at around 1.8 mm, which can not only achieve plug flow to reduce back mixing, but also significantly reduce system pressure drop. At the same time, the axial compressive strength of 8MPa and the radial bending strength of 3MPa ensure structural stability. -6 / ℃ thermal expansion coefficient gives it excellent thermomechanical properties and provides an ideal carrier platform for catalyst active components.
[0013] The rear plate structure described in the present invention is a layered catalyst carrier structure with parallel airflow channels. Its basic structure is a regular flow channel system composed of alternating flat corrugated plates and straight partitions. This structure uses the same cordierite ceramic matrix material as the honeycomb type, and is made into 0.3mm thick corrugated plates through a precision extrusion molding process. The corrugation shape is a continuous sinusoidal waveform or trapezoidal wave, the wave height is controlled at 2-3mm, and the wavelength is maintained at an equal spacing of 5-6mm. These corrugated plates and flat partitions are stacked at a ratio of 1:1 to form highly consistent triangular or approximately rectangular airflow channels with an equivalent channel diameter of about 3.5mm. The surface is covered with a 20-30μm thick γ-alumina coating as an active component carrier. A special concave-convex mortise and tenon structure is used for positioning and assembly between the plates, and the contact surface is polished to ensure an assembly accuracy of within 0.05mm, and the overall porosity is maintained in the range of 65-70%. The surface of the corrugated plate is designed with a micro-groove texture of 0.1-0.2mm deep, combined with hemispherical protrusions at intervals of 0.5-1mm, which enhance the airflow disturbance while maintaining a low pressure drop. The uniqueness of this structure lies in the gradual design of the corrugation amplitude gradually reducing along the airflow direction. The inlet section adopts a 3mm wave height to enhance turbulent mixing, and the outlet section is reduced to 1.5mm wave height to reduce resistance. The length of the transition zone accounts for about 1 / 3 of the overall length. All plate edges are equipped with a 2mm wide reinforcement frame, and an integral structure is formed by high-temperature sintering to ensure that the bending strength of more than 1.5MPa is maintained in a high-temperature flue gas environment. At the same time, the corrugated nodes are locally thickened to 0.4mm to resist airflow scouring. This carefully designed geometric structure enables the gas to form a specific secondary flow pattern in the channel, which not only ensures the effective renewal of the boundary layer on the catalyst surface, but also controls the pressure drop to 60-70% of the honeycomb structure, achieving the optimal balance between mass transfer efficiency and energy consumption.
[0014] According to a preferred embodiment of the present invention, in step S3, the aperture of the porous ammonia injection grid is 2 mm, and the porosity is 40%; the porous ammonia injection grid is installed 1 meter before the reactor inlet; the reaction temperature of the reaction system is 180-220 ° C, and the space velocity is 3000h -1 When operating under the specified conditions, the oxygen content in the flue gas shall not be less than 5%.
[0015] According to a preferred embodiment of the present invention, the porous ammonia injection grid is purchased from Jiangsu Ruicheng Metal Technology Co., Ltd.
[0016] According to a preferred embodiment of the present invention, the ammonia is purchased from Tianjin Yongteng Gas Sales Co., Ltd.
[0017] According to a preferred embodiment of the present invention, the online NO x The monitoring instrument was purchased from Shenzhen Yifan Technology Co., Ltd.
[0018] The ammonia gas injected in the present invention is adsorbed and dissociated into NH x Species. In the redox cycle provided by Ce-Mn active components (Ce 4+ / Ce 3+ , Mn 4+ / Mn 3+ ) under the action of NH x with NO x Selective redox reaction occurs to generate N2 and H2O. Precisely controlled NH3 / NO x This avoids excess or deficiency of ammonia.
[0019] According to a preferred embodiment of the present invention, in step S4, the shell and tube waste heat boiler is made of stainless steel, and the volume of the shell and tube waste heat boiler is 316L.
[0020] According to a preferred embodiment of the present invention, the shell and tube waste heat boiler is purchased from Shandong Lujie Thermal Energy Equipment Co., Ltd.
[0021] In this invention, when the high-temperature flue gas after denitration passes through the shell-and-tube heat exchanger, the heat is transferred to the working medium (water / steam) through the stainless steel wall. The corrosion resistance of 316L material ensures long-term stable heat transfer in sulfur-containing flue gas environments.
[0022] According to a preferred embodiment of the present invention, the modification step of the modified catalyst comprises: S1, place the ZSM-5 molecular sieve in a muffle furnace, heat to 550°C, and calcine for 4 hours. After cooling, immerse in a 0.1 mol / L nitric acid solution and ultrasonicate. S2, prepare a mixed solution of deionized water containing cerium nitrate hexahydrate and manganese acetate tetrahydrate. Mix the pretreated ZSM-5 molecular sieve with the solution in a mass ratio of 1:10 and stir in a water bath. Then transfer to a microwave reactor and irradiate. Separate the solid product by filtration, wash it three times with ethanol, and dry it in an oven. Finally, calcine it to 450°C under a nitrogen atmosphere to obtain a Ce-Mn active component-loaded molecular sieve. S3, Ce-Mn active component loaded molecular sieve atomic layer deposition, the ALD reaction chamber temperature was set to 200 ° C, the vaporization chamber temperature of trimethylaluminum and water was 25 ° C and 30 ° C, respectively, and nitrogen was introduced as a carrier gas; each deposition cycle consisted of four steps: first, TMA gas was introduced for 0.1 seconds, followed by nitrogen purge for 10 seconds; then, water vapor was introduced for 0.1 seconds, and nitrogen purge was performed again for 10 seconds; this cycle was repeated 50 times to obtain a molecular sieve coated with a γ-alumina shell layer; S4, the molecular sieve coated on the surface of the deposited alumina shell is placed in a tube furnace and vacuumed to 10 -3After 150°C, the temperature was raised to 150°C. 3-aminopropyltriethoxysilane vapor was introduced; the temperature was raised to 300°C under nitrogen protection and kept constant to fully cure the silane coupling agent.
[0023] According to a preferred embodiment of the present invention, the ZSM-5 molecular sieve is purchased from PetroChina Company Limited.
[0024] According to a preferred embodiment of the present invention, the muffle furnace is purchased from Nanjing Kejie Testing Technology Development Co., Ltd. and is model AFD1200-40.
[0025] According to a preferred embodiment of the present invention, the nitric acid solution is purchased from Zibo Kunmao Economic and Trade Co., Ltd.
[0026] According to a preferred embodiment of the present invention, the cerium nitrate hexahydrate is purchased from Zhengzhou Aikemu Chemical Co., Ltd.
[0027] According to a preferred embodiment of the present invention, the manganese acetate tetrahydrate is purchased from Jiangsu Runfeng Synthetic Technology Co., Ltd.
[0028] According to a preferred embodiment of the present invention, the deionized water is purchased from Shanghai Binrun Environmental Protection Technology Co., Ltd.
[0029] According to a preferred embodiment of the present invention, the microwave reactor was purchased from Dongguan Huaqing Microwave Equipment Manufacturing Co., Ltd.
[0030] According to a preferred embodiment of the present invention, the ethanol is purchased from Nantong Runfeng Petrochemical Co., Ltd.
[0031] According to a preferred embodiment of the present invention, the oven is purchased from Shanghai Boxun Industrial Co., Ltd.
[0032] According to a preferred embodiment of the present invention, the ALD equipment is purchased from Jiangsu Microguide Nanotechnology Co., Ltd.
[0033] According to a preferred embodiment of the present invention, the TMA gas is trimethylaluminum.
[0034] According to a preferred embodiment of the present invention, the TMA gas is purchased from Jiangsu Yongjian Chemical Co., Ltd.
[0035] According to a preferred embodiment of the present invention, the tubular furnace is purchased from Zhengzhou Kejia Electric Furnace Co., Ltd.
[0036] According to a preferred embodiment of the present invention, the 3-aminopropyltriethoxysilane is purchased from Shanghai Hansi Chemical Co., Ltd.
[0037] According to a preferred embodiment of the present invention, the silane coupling agent is purchased from Hubei Jianghan New Materials Co., Ltd., model KH550.
[0038] According to a preferred embodiment of the present invention, in step S1, the molar ratio of SiO2 to Al2O3 in the ZSM-5 molecular sieve is 80, and the temperature is raised to 550°C at a heating rate of 5°C / min; the power of the ultrasonic treatment is 300W, and the treatment time is 30 minutes.
[0039] During the calcination process at 550°C, the molecular sieve framework undergoes dehydroxylation, generating Lewis acid sites. The nitric acid treatment further regulates the acid distribution through proton exchange: + Replacement framework Al 3+ Nearby Na + , forming Brønsted acid sites (≡Si-OH-Al≡). The cavitation effect generated by ultrasonic treatment creates microjets within the molecular sieve pores, effectively removing pore blockages and increasing the specific surface area by approximately 30%. The specific SiO2 / Al2O3 molar ratio (80) ensures appropriate acid density and thermal stability.
[0040] According to a preferred embodiment of the present invention, in step S2, the molar ratio of cerium to manganese is 1:2; the stirring time in the water bath is 6 hours; the radiation treatment power is 800 W, the temperature is 80° C., and the time is 30 minutes; the drying in the oven is 12 hours, and the drying temperature is 110° C.; the heating rate of the calcination is 2° C. / min; and the calcination time is 3 hours.
[0041] Under the water bath conditions of the present invention, Ce 3+ and Mn 2+ Entering the molecular sieve supercage through ion exchange. Microwave radiation induces dielectric heating, which promotes the deep diffusion of metal precursors: Ce 3+ Mn preferentially occupies the β cage site of the molecular sieve. 2+ Distributed within the α-cage. During calcination, a unique phase forms: CeO2 nanoparticles (5-8 nm) anchored at the pore openings, and Mn2O3 clusters (2-3 nm) dispersed within the pores. Strong Ce-Mn interactions create this unique coordination environment, creating low-temperature SCR active centers.
[0042] According to a preferred embodiment of the present invention, in step S3, the flow rate of the nitrogen gas is 200 sccm; the pressure of the reaction chamber is 0.5 Torr when TMA gas is introduced; the pressure of the reaction chamber is 0.1 Torr when nitrogen is purged; the pressure of the reaction chamber is 0.5 Torr when water vapor is introduced, and the pressure of the reaction chamber is 0.1 Torr when nitrogen is purged again; the thickness of the γ-alumina shell layer is 80 nm.
[0043] The ALD process in the present invention follows a self-limiting surface reaction mechanism: when TMA is chemically adsorbed, -CH3 reacts with -OH on the molecular sieve surface to release CH4 to form Al-CH 3*Surface; H2O and Al-CH 3* Reaction to generate Al-OH * and release CH4; 0.1nm Al2O3 is deposited in each cycle, and after 50 cycles, a gradient shell is formed: the side close to the support is amorphous Al2O3 (favorable for stress release), and the outside is γ-Al2O3 (thermally stable phase). The mesopores (3-5nm) in the shell allow gas diffusion but block Ca 2+ migrate.
[0044] According to a preferred embodiment of the present invention, in step S4, the rate of introducing 3-aminopropyltriethoxysilane vapor is 5 mL / min; the duration is 2 h; the temperature is raised to 300° C. at a rate of 3° C. / min under nitrogen protection, and the constant temperature treatment time is 2 h.
[0045] In this invention, APTES is grafted via a three-step reaction: ethoxyl hydrolysis (Si(OC2H5)3 + 3H2O → Si(OH)3 + 3C2H5OH); condensation dehydration (Si(OH)3 + Al-OH → Si-O-Al + 2H2O); and amino group alignment (-NH2 groups pointing toward the surface at an angle of approximately 60°), forming a molecular "ammonia capture network." Heat treatment fully solidifies the Si-O-Al bonds and simultaneously oxidizes some -NH2 to -NH-, creating an electron delocalized system and enhancing the synergistic NH3 adsorption-activation effect.
[0046] The beneficial effects of the present invention are: This invention has achieved a breakthrough in the field of lime kiln flue gas treatment through innovative process design and catalyst modification technology. In terms of denitrification performance, the use of a specially structured modified catalyst module, combined with an intelligent ammonia injection control system, achieves efficient denitrification under low-temperature conditions, which is significantly better than the performance of traditional catalysts under the same temperature conditions. The unique core-shell structure catalyst effectively blocks the penetration of harmful components in lime dust through a protective layer, fundamentally solving the industry pain point of catalyst poisoning and deactivation. The optimized ammonia-nitrogen ratio control keeps ammonia escape at an extremely low level, significantly reducing the risk of secondary pollution.
[0047] In terms of system operational efficiency, this invention creatively integrates multiple processing units into an integrated process flow. The highly efficient pretreatment device can quickly separate large dust particles, creating ideal conditions for subsequent denitrification. The innovative reactor structure significantly reduces system resistance and energy consumption. The design concept of utilizing the flue gas's own waste heat to maintain the reaction temperature completely avoids the traditional process's reliance on auxiliary heating devices, significantly improving system energy efficiency. The rational configuration of the waste heat recovery unit further optimizes overall energy efficiency.
[0048] Regarding the catalyst's long-term stability, a protective layer constructed through advanced surface treatment technology, combined with a specialized surface modification process, ensures excellent durability in high-calcium environments. The modified catalyst maintains stable performance under high-load conditions, significantly improving processing capacity. The entire system features a compact design, significantly reducing footprint and extending maintenance cycles. These technological innovations not only overcome the technical difficulties of lime kiln flue gas treatment but also provide a valuable solution for similar industrial flue gas treatment. DETAILED DESCRIPTION
[0049] The following specific implementation methods are only used to further illustrate the present application and should not be understood as limiting the scope of protection of the present application. Technicians in this field may make some non-essential improvements and adjustments to the present application based on the above application content. One embodiment:
[0050] Example 1:
[0051] Flue gas pretreatment: The lime kiln flue gas is introduced into a cyclone separator with a diameter of 1.2 meters and a height-to-diameter ratio of 3:1 at a tangential velocity of 15m / s. The residence time of the flue gas in the separator is strictly controlled at 2.5 seconds.
[0052] Catalyst Loading: The modified catalyst is processed into a honeycomb-plate composite module with a pore density of 300 cpsi and a wall thickness of 0.3 mm, for a total loading volume of 3.2 m³. Layered according to the flue gas flow direction, the first 20% of the volume (0.64 m³) utilizes a honeycomb structure to enhance turbulent mixing, while the last 80% of the volume (2.56 m³) utilizes a plate structure to reduce system pressure drop. The honeycomb structure features a regular hexagonal pore with a 1.2 mm pore diameter. The plate structure consists of alternating corrugated plates and straight baffles, with a corrugation height of 2 mm and a wavelength of 5 mm.
[0053] Denitrification reaction control: A porous ammonia spraying grid with a pore size of 2mm and an opening rate of 40% is installed 1 meter before the reactor inlet. x The monitor uses real-time data to dynamically adjust the ammonia injection volume and control the NH3 / NO x The molar ratio is 0.9. The flue gas flow rate is 9600Nm³ / h, corresponding to an air velocity of 3000h -1 The reaction temperature was maintained at 195±5℃, the oxygen content in the flue gas was 6.2vol%, the ammonia injection rate was 12.7kg / h, and the flow accuracy of ±0.5% was achieved through the PID control system.
[0054] Waste Heat Recovery: After denitrification, the flue gas enters a 316L stainless steel shell-and-tube waste heat boiler with a heat exchange area of 85m². Flue gas passes through the tube side, heating the shell-side water to produce 0.8MPa saturated steam. Steam production reaches 1.2t / h, with a heat recovery efficiency of 78%.
[0055] Catalyst preparation: 2.5 kg of ZSM-5 molecular sieve with a SiO2 / Al2O3 molar ratio of 80 was calcined in a muffle furnace at 550°C at a heating rate of 5°C / min for 4 hours. After cooling, it was immersed in 500 mL of 0.1 mol / L nitric acid solution and ultrasonically treated at 300 W power for 30 minutes.
[0056] A mixed solution containing 148.2 g of cerium nitrate hexahydrate and 122.1 g of manganese acetate tetrahydrate (cerium:manganese molar ratio 1:2) was prepared, and 250 g of pretreated molecular sieves were added. The mixture was stirred in a 60°C water bath for 6 hours. The mixture was transferred to a microwave reactor and irradiated at 800 W and 80°C for 30 minutes. After filtration, the mixture was washed three times with ethanol, dried at 110°C for 12 hours, and finally calcined at 450°C under a nitrogen atmosphere at a rate of 2°C / min for 3 hours.
[0057] 500g of the calcined material was placed in the ALD reactor, set at 200°C, 25°C for the TMA vaporizer, 30°C for the water vaporizer, and 200 sccm for the nitrogen flow rate. Each deposition cycle consisted of 0.1 second of TMA gas flow (chamber pressure 0.5 Torr), 10 seconds of nitrogen purge (0.1 Torr), 0.1 second of water vapor flow (0.5 Torr), and 10 seconds of nitrogen purge (0.1 Torr). This cycle was repeated 50 times, resulting in an 80nm thick γ-alumina shell.
[0058] The deposited material was placed in a tube furnace and vacuumed to 10 -3 Pa, then the temperature was raised to 150°C, and 3-aminopropyltriethoxysilane vapor was introduced at a rate of 5 mL / min for 2 hours. Subsequently, the temperature was raised to 300°C at a rate of 3°C / min under nitrogen protection and kept constant at this temperature for 2 hours to fully cure the silane coupling agent.
[0059] Example 2:
[0060] The specific implementation method is the same as that of Example 1, except that the process conditions are adjusted to: flue gas flow rate 7200Nm³ / h (space velocity 2250h -1 ); Catalyst loading volume 3.2m 3 (honeycomb type 0.8m³ + plate type 2.4m³); ammonia injection rate 9.5kg / h (NH3 / NO x= 0.88); reaction temperature 205°C. Catalyst preparation: ZSM-5 3.0 kg; cerium nitrate hexahydrate 177.8 g + manganese acetate tetrahydrate 146.5 g; ALD cycles 40 (shell ≈ 64 nm).
[0061] Example 3:
[0062] The specific implementation method is the same as that of Example 1, except that the process conditions are adjusted to: flue gas flow rate 12000 Nm³ / h (space velocity 3750 h -1 Catalyst loading volume: 3.2m³ (honeycomb type 0.48m³ + plate type 2.72m³); ammonia injection volume: 15.9kg / h (NH3 / NO x = 0.91); reaction temperature 185°C. Catalyst preparation: ZSM-5 2.0 kg; cerium nitrate hexahydrate 118.5 g + manganese acetate tetrahydrate 97.7 g; ALD cycles 60 (shell ≈ 96 nm).
[0063] Comparative Example 1 The specific implementation method is the same as that of Example 1, except that a single SCR reactor (all honeycomb type); a V2O5-WO3 / TiO2 catalyst; and a space velocity of 2000h -1 , reaction temperature 220℃.
[0064] Comparative Example 2 The specific implementation method is the same as that of Example 1, except that the ALD deposition step is omitted.
[0065] Comparative Example 3 The specific implementation method is the same as that of Example 1, except that the single structure reactor adopts a honeycomb structure.
[0066] Performance Testing The preparation processes of Examples 1-3 and Comparative Examples 1-3 were tested and calculated according to the following method: 1. Denitrification efficiency: According to the standard GB / T 16157-2018; the flue gas analyzer (Testo 350) continuously monitors the NO inlet and outlet of the reactor. x Concentration, calculation: (inlet NO x -Export No. x ) / entranceNO x ×100%. Sampling location: reactor inlet and outlet flanges.
[0067] 2. Ammonia escape: Conducted in accordance with standard HJ 533-2018; real-time monitoring using a laser ammonia analyzer (Siemens LDS 6) with a sampling probe equipped with a ceramic filter (200°C constant temperature). Sampling location: Centerline of the reactor outlet flue.
[0068] 3. Calcium poisoning analysis: Conducted in accordance with ISO 18560-2:2015; post-operation catalyst sampling → XRF analysis for Ca content; BET surface area measurement (Micromeritics ASAP 2460). Sampling location: Sampling point in the middle of the catalyst module.
[0069] 4. System pressure drop: Conducted according to GB / T 1236-2017; a differential pressure transmitter (Rosemount 3051) measures the pressure difference between the reactor inlet and outlet. Sampling location: 1 m straight pipe section before and after the reactor.
[0070] 5. Energy consumption: Conducted in accordance with GB / T 15316-2020. A power meter (Class 0.5) records fan / pump power consumption; a steam flow meter measures waste heat recovery. Sampling location: Power distribution cabinets for all electrical equipment.
[0071] 6. Test results: Table 1: Test results of various embodiments and comparative examples
[0072] As can be seen from Table 1, the present invention has comprehensively solved the five major technical problems in the field of lime kiln flue gas treatment through systematic test data verification. In terms of low-temperature denitrification efficiency, the Ce-Mn / ZSM-5@Al2O3 catalyst is used in combination with a composite reactor structure to achieve a denitrification efficiency of more than 90% under 180-220°C conditions, which is 32 percentage points higher than the traditional process. This is mainly due to the oxygen vacancies formed by the gradient distribution of Ce-Mn oxides in the catalyst and the enhanced NH3 adsorption capacity due to aminosilane modification. In response to the problem of calcium poisoning of the catalyst, the 80nm dense Al2O3 shell constructed by ALD technology controls the Ca deposition amount below 1.1mg / g after 15 months of operation, effectively protecting the internal active components. In terms of ammonia escape control, the turbulent effect generated by the front-stage honeycomb structure and the precise online feedback system are used to stabilize the ammonia escape concentration within 3.1ppm, which is 63% lower than the traditional process. This is due to the optimized airflow distribution and real-time control of NH3 / NO x The significant reduction in system energy consumption is reflected in three aspects: the flue gas waste heat self-maintains the reaction temperature, eliminating the need for traditional electric heating devices, the composite structure design reduces the pressure drop by 35%, the waste heat boiler achieves 78% heat recovery, and the overall energy consumption is reduced by 38%. The equipment is compact through integrated process design and high air velocity (3000h -1) operation, reducing floor space by 45%. The integrated layout of cyclone dust removal, catalytic denitrification, and waste heat recovery eliminates the connecting pipes and transition space required for traditional split-system processes. Particularly noteworthy is that while maintaining high performance, the catalyst's resistance to calcium poisoning extends its service life to five times that of traditional catalysts. The use of a plate-type rear section reduces pressure drop by 35% while increasing volume by only 10%. These innovations collectively constitute the core technological advantages of this invention, providing a reliable solution for the treatment of medium- and low-temperature industrial flue gases, such as those from lime kilns.
[0073] The above-described embodiments merely illustrate several implementations of the present invention. While the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the present invention. It should be noted that a person skilled in the art would be able to make numerous variations and improvements without departing from the spirit of the present invention, and all such variations and improvements fall within the scope of protection of the present invention.
Claims
1. A lime kiln denitrification integrated flue gas treatment process, characterized in that: The following steps are involved: S1, the flue gas enters the cyclone separator at a tangential velocity with a residence time of 2.5s; S2, processing the modified catalyst into a honeycomb-plate composite module; arranging it in layers according to the direction of flue gas flow, with the front 20% volume being a honeycomb structure and the rear 80% volume being a plate structure; S3, install a porous ammonia injection grid at the inlet of the cyclone reactor, according to the online NO x The monitor's real-time data dynamically adjusts the ammonia injection volume to maintain the NH3 / NO x The molar ratio is 0.9; S4, after denitrification, the flue gas enters the shell and tube waste heat boiler.
2. The lime kiln denitrification integrated flue gas treatment process according to claim 1, characterized in that: In step S1, the tangential velocity is 15 m / s; the diameter of the cyclone separator is 1.2 meters, and the height-to-diameter ratio is 3:
1.
3. The lime kiln denitrification integrated flue gas treatment process according to claim 1, characterized in that: In step S2, the honeycomb-plate composite module has a pore density of 300 cpsi and a wall thickness of 0.3 mm.
4. The lime kiln denitrification integrated flue gas treatment process according to claim 1, characterized in that: In step S3, the porous ammonia injection grid has a pore size of 2 mm and an opening rate of 40%; the porous ammonia injection grid is installed 1 meter before the reactor inlet; the reaction temperature of the reaction system is 180-220 ° C, and the space velocity is 3000h -1 When operating under the specified conditions, the oxygen content in the flue gas shall not be less than 5%.
5. The lime kiln denitrification integrated flue gas treatment process according to claim 1, characterized in that: In step S4, the shell and tube waste heat boiler is made of stainless steel, and the volume of the shell and tube waste heat boiler is 316L.
6. The lime kiln denitrification integrated flue gas treatment process according to any one of claims 1 to 5, characterized in that: The modification step of the modified catalyst comprises: S1, placing the ZSM-5 molecular sieve in a muffle furnace, heating to 550°C, calcining for 4 hours, and then immersing it in a 0.1 mol / L nitric acid solution after cooling, and ultrasonically treating it; S2, preparing a mixed solution of deionized water containing cerium nitrate hexahydrate and manganese acetate tetrahydrate, mixing the pretreated ZSM-5 molecular sieve and the solution in a mass ratio of 1:10, placing the mixture in a water bath with stirring, and then transferring the mixture to a microwave reactor for irradiation treatment; separating the solid product by suction filtration, washing it three times with ethanol, and drying it in an oven, and finally calcining it to 450° C. under a nitrogen atmosphere to obtain a Ce-Mn active component-loaded molecular sieve; S3, Ce-Mn active component loaded molecular sieve atomic layer deposition, the ALD reaction chamber temperature was set to 200 ° C, the vaporization chamber temperature of trimethylaluminum and water was 25 ° C and 30 ° C, respectively, and nitrogen was introduced as a carrier gas; each deposition cycle consisted of four steps: first, TMA gas was introduced for 0.1 seconds, followed by nitrogen purge for 10 seconds; then, water vapor was introduced for 0.1 seconds, and nitrogen purge was performed again for 10 seconds; this cycle was repeated 50 times to obtain a molecular sieve coated with a γ-alumina shell layer; S4, the molecular sieve coated on the surface of the deposited alumina shell is placed in a tube furnace and vacuumed to 10 -3 After Pa, the temperature is raised to 150° C., and 3-aminopropyltriethoxysilane vapor is introduced; the temperature is raised to 300° C. under nitrogen protection, and constant temperature treatment is performed to fully cure the silane coupling agent.
7. The lime kiln denitrification integrated flue gas treatment process according to claim 6, characterized in that: In step S1, the molar ratio of SiO2 to Al2O3 in the ZSM-5 molecular sieve is 80, and the temperature is raised to 550°C at a heating rate of 5°C / min; the power of the ultrasonic treatment is 300W, and the treatment time is 30 minutes.
8. The lime kiln denitrification integrated flue gas treatment process according to claim 6, characterized in that: In step S2, the molar ratio of cerium to manganese is 1:2; the stirring time in the water bath is 6 hours; the radiation treatment power is 800 W, the temperature is 80° C., and the time is 30 minutes; the drying in the oven is 12 hours, and the drying temperature is 110° C.; the heating rate of the calcination is 2° C. / min; and the calcination time is 3 hours.
9. The lime kiln denitrification integrated flue gas treatment process according to claim 6, characterized in that: In step S3, the flow rate of the nitrogen gas is 200 sccm; the pressure of the reaction chamber is 0.5 Torr when TMA gas is introduced; the pressure of the reaction chamber is 0.1 Torr when nitrogen is purged; the pressure of the reaction chamber is 0.5 Torr when water vapor is introduced, and the pressure of the reaction chamber is 0.1 Torr when nitrogen is purged again; the thickness of the γ-alumina shell layer is 80 nm.
10. The lime kiln denitrification integrated flue gas treatment process according to claim 6, characterized in that: In step S4, 3-aminopropyltriethoxysilane vapor is introduced at a rate of 5 mL / min and lasts for 2 h. Under nitrogen protection, the temperature is raised to 300° C. at a rate of 3° C. / min, and the constant temperature treatment time is 2 h.
Citation Information
Patent Citations
Integral desulfurization and denitration complete device by catalytic reduction ammonia method for small and medium boilers
CN202460474U
Low-temperature selective catalytic reduction denitrification system of cement kiln
CN203577637U
Purifying method of combustion waste gas and catalyst used for this method
JP1996080424A